Optimization of wind-powered dust removal parameters for photovoltaics solar panel - Attia, Osam Hassan (2019)
The dust accumulation is an undesirable phenomenon in a solar plant environment. The procedure for removing dust using traditional techniques is capital and labour intensive. Additionally, most of the cleaning techniques consumed power from energy produced by the solar system. Therefore, the aim of this study is to develop a wind powered dust removal technique from the solar panel. This was done by transforming wind energy into mechanical energy as a new approach to sustainability via mechanical vibrator. The mechanical vibrator is attached to the panel and will produce a harmonic excitation force to overcome the adhesion force of dust onto solar panel surface. In this study, five levels of vibration forces were acquired through pre-experiment by varying the wind speed, while the range of the other working independent parameters such as dust quantity, dust size, wind speed and tilt angle of the solar panel were adopted from the previous studies. To determine how each of the parameters affects the dust removal index (DRI), a screening process was conducted using Plackett- Burman design (PBD) in Minitab with 12 runs each for the system with and without vortex generator. In response surface methodology (RSM) experiment, 50 runs were done for the optimizations of the working parameters with respect to DRI. The selection process was generally followed by statistical analysis known as Analysis of variance (ANOVA). Response Surface methodology (RSM) is an optimization method, which has been applied to optimization problems and provided a mathematical model for the DRI. Another model was built using another optimization technique called particle swarm optimization (PSO) and was used to verify the RSM model with modified code in MATLAB software. The proof of concept experiment clearly shows that with an increase in wind speed the vibrating force increases accordingly. Also, according to the screening process with PBD, the studied parameters have been arranged in order of their effect either high or low based on the assessment criteria outlined in PBD with and without vortex generators. The arrangement of the parameters based on their effect on DRI without VGs from high to low is different from the arrangement with VGs; this indicated that VGs have asignifacant effect on parameters. The incorporation of the vortex generator, the levels and behaviour of the parameters were changed and the mean value of DRI increased from 0.50 to 0.58. Analysis for the optimization of the working parameters reveals that RSM-DRI model revealed high significant performance with CoV and SD value of 4.51% and 0.0448 respectively. While PSO-DRI model has CoV and SD value of 4.55% and 0.0445 respectively. Therefore, RSM model helps a designer to select the most suitable site for the solar plant provided that the tilt angle is within the range of 15° to 35°. In conclusion, the use of wind energy via mechanical vibrator for dust removal has an efficiency of 91% when compared with a demonstrative electric vibrator for cleaning the same quantity of dust from the solar panel.